Ways of being Roman : discourses of identity in the Roman West - Revell, Louise (Oxbow Books, 2016)
"This book examines the question of identity in the Roman provinces of the western empire. It takes an innovative approach in looking at the wider discourses or ideologies through which an individual sense of self was learnt and expressed. This wide-ranging survey considers ethnic identity, status, gender, and age. Rather than constructing a paradigm of the 'ideal' of any specific aspect of personal identity, it looks at some of the wider cultural ideas which were drawn upon in differentiating groups of people and the variability within this. It focuses on the daily and mundane practices of everyday life through which identities were internalised and communicated"--Provided by publisher.